Altered orbitofrontal activity and dorsal striatal connectivity during emotion processing in dependent marijuana users after 28 days of abstinence - Zimmermann, Kaeli; Yao, Shuxia; Heinz, Marcel; Zhou, Feng; Dau, Wolfgang; Banger, Markus; Weber, Bernd; Hurlemann, René; Becker, Benjamin (Psychopharmacology, 2018)
Rationale Intact cognitive and emotional functioning is vital for the long-term success of addiction treatment strategies. Accumulating evidence suggests an association between chronic marijuana use and lasting alterations in cognitive brain function. Despite initial evidence for altered emotion processing in dependent marijuana users after short abstinence periods, adaptations in the domain of emotion processing after longer abstinence remain to be determined. Objective and methods Using task-based and resting state fMRI, the present study investigated emotion processing in 19 dependent marijuana users and 18 matched non-using controls after an abstinence period of > 28 days. Results Relative to the control subjects, negative emotional stimuli elicited increased medial orbitofrontal cortex (mOFC) activity and stronger mOFC-dorsal striatal and mOFC-amygdala functional coupling in dependent marijuana users ( p < 0.022, FWE-corrected). Furthermore, mOFC-dorsal striatal functional connectivity was increased at rest in marijuana users ( p < 0.03, FWE-corrected). Yet, processing of positive stimuli and subjective ratings of valence and arousal were comparable in both groups. Conclusions Together, the present findings provide the first evidence for persisting emotion processing alterations in dependent marijuana users. Alterations might reflect long-term neural adaptations as a consequence of chronic marijuana use or predisposing risk factors for the development of marijuana dependence.